Effect of temporal thermal field on quality of semi-solid metal formed components - Asnul Hadi, Ahmad (2015)
This thesis presents an investigation of the effect of the semi-solid processing parameters on aluminium alloy 7075. In particular, this thesis focuses on the effect of the temporal thermal fields. Thermal analysis (TA) was initially performed in order to determine suitable processing conditions and understand the relationship between fraction solid and temperature. A specially designed chamber was used to achieve the cooling rates of 0.13 °CIs and different cooling medium were used to replicate the cooling rates of 0.32 °C/s, 0.36 °C/s and 0.39 °C/s. Different cooling rates had a marginal effect on the liquidus, eutectic and solidus phase change temperatures. The coherency point temperatures were also found to be weakly dependent on the cooling rates within the range investigated within this work. The fraction solid was however found to be strongly dependent on temperature. At temperatures higher than the coherency point (approximately 0.20 f for all cooling rates), the slopes of the fraction solid curves were not very steep which indicates that the fraction solid is sensitive to temperature fluctuation within this region. Based on this information gained from TA, globular microstructure feedstock billets suitable for SSM forming were produced by the direct thermal method (DTM). Spheroidal primary phase microstructures were best produced with the combination of 665 °C pouring temperature and 60 s holding time. The average microstructure primary phase diameter from DTM was measured to be within the range of 82 to 123 pm and circularity between 0.55 and 0.67. Higher pouring temperature was found to produce larger amount of secondary phase which was also determined in this work to lead to greater fluidity of the semi-solid material. The fluidity of the DTM feedstock billets were evaluated by a compression test at 185 kN. The formability of the feedstock billets was significantly influenced by the primary grain circularity and secondary (liquid) phase content within feedstock billets, with grain size having least effect. The average primary phase diameter and circularity after the forming operation were found to be in the range of 110 to 136 pm and 0.59 to 0.71 respectively. Tensile, hardness and porosity were examined for the feedstock billet after forming. Structures with greater amount of secondary phase were found to have the lowest strength and hardness properties. Processing parameters that led to samples with increased density (685 °c pouring temperature and 20 s holding time) were found to have increased strength and hardness. Smaller grain structures produced higher CTE and thermal dimension expansion values. The findings of this work have established the DTM feedstock production processing conditions which can enable the thixoforming of semi-solid 7075. Such enhanced formability is a priority when processing alloys of low fluidity such as 7075 wrought alloy.